2007
DOI: 10.1016/j.jfoodeng.2007.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional reconstruction of irregular foodstuffs

Abstract: Three-dimensional reconstruction of general solid food materials was performed using a reverse engineering method based on a surface cross-sectional design. Digital images of cross-sections of irregular multi-dimensional foodstuffs were acquired using a computer vision system, and image processing was performed to obtain the actual boundaries. These boundaries were then approximated by closed B-spline curves, which were assembled through a lofting technique to construct a geometrical representation of food mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 23 publications
(22 reference statements)
3
44
0
1
Order By: Relevance
“…In the publications on the use of 3D scanning in food examinations, the authors mainly focused their attention primarily on issues of accuracy of product volume estimation. For example, Goñi et al (2007) using 3D scanning technique determined the volume of, e.g., pieces of meat with mean estimation error lower than 2%.…”
Section: Correlation Between Density and Chemical Composition Of Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…In the publications on the use of 3D scanning in food examinations, the authors mainly focused their attention primarily on issues of accuracy of product volume estimation. For example, Goñi et al (2007) using 3D scanning technique determined the volume of, e.g., pieces of meat with mean estimation error lower than 2%.…”
Section: Correlation Between Density and Chemical Composition Of Meatmentioning
confidence: 99%
“…As an example, Uyar and Erdoğdu (2009) determined that there exists a possibility to use a 3D scanning technique for the determination of volume of food products with irregular shapes, such as bananas, pears, and eggs. Goñi et al (2007) using 3D scanning technique determined the volume of pieces of meat. The 3D scanning method was also used for the determination of cereal product porosity, and the authors underlined the fact that using this method does not require analytic preparation of a sample (Russ 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modelling of a product shape based on conventional methods is a laborious process, in particular in products with irregular shape (Goni et al, 2007). Fruit and seed dimensions are very often determined with the use of image analysis software and measuring tools such as calipers and micrometers (Frączek and Wróbel, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The object is sectioned along a selected axis and section measurements are used to estimate surface area and volume of a reconstructed object. Goñi et al [9] used this method to estimate the surface area and volume of apples and meat pieces with less than 2% estimation error. They concluded that applying lofting technique allows obtaining an accurate representation of the real shape of irregular multi-dimensional foodstuffs and this method demonstrated its ability to correctly predict volume and surface area of general objects, including those of low symmetry and sphericity.…”
Section: Introductionmentioning
confidence: 99%